2014
DOI: 10.1007/s00424-014-1454-x
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channel blockers as neuroprotective agents

Abstract: T-type calcium channels are expressed in many diverse tissues, including neuronal, cardiovascular, and endocrine. T-type calcium channels are known to play roles in the development, maintenance, and repair of these tissues but have also been implicated in disease when not properly regulated. Calcium channel blockers have been developed to treat various diseases and their use clinically is widespread due to both their efficacy as well as their safety. Aside from their established clinical applications, recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 81 publications
0
48
0
Order By: Relevance
“…Of the four selected compounds, manidipine, lacidipine, and benidipine target L-type calcium channels and are clinically used as antihypertensive agents [34], whereas lomerizine targets both Land T-type calcium channels and is generally used in the clinical treatment of migraines [35], as well as the experimental treatment of glaucoma and optic nerve injury [36].…”
Section: Ccbs Inhibit Sphere Formation and Induce Cell Death In Ovarimentioning
confidence: 99%
“…Of the four selected compounds, manidipine, lacidipine, and benidipine target L-type calcium channels and are clinically used as antihypertensive agents [34], whereas lomerizine targets both Land T-type calcium channels and is generally used in the clinical treatment of migraines [35], as well as the experimental treatment of glaucoma and optic nerve injury [36].…”
Section: Ccbs Inhibit Sphere Formation and Induce Cell Death In Ovarimentioning
confidence: 99%
“…This provides a potential therapeutic target, by using drugs that modulate the amount of free Ca 2+ in the cell. Ca 2+ channel blockers, such as those from the dihydropyridine family, may be used to lessen the increase in intracellular Ca 2+ seen in aged neurons [ 82 ]. A step towards replicating the complex architecture of the CNS and assessing Ca 2+ blockade was performed by Chan et al [ 83 ] who used brain slices prepared from a MPTP mouse model for PD.…”
Section: Increased Intracellular Ca 2+ Induces mentioning
confidence: 99%
“…The present study demonstrated that an herbal medicine called quercetin, at 50 μM concentration, protected SH-SY5Y cells from bupivacaine-induced cellular death, and was as effective as mibefradil, one T-type calcium channel blocker, at 10 μM concentration. The neuro-protective effects of T-type calcium channel blockers (such as mibefradil) have been reported before [10]. For example, Bancila et al found that mibefradil administration prevented neuronal death after ischemia in a global ischemia rat model [11].…”
Section: Discussionmentioning
confidence: 94%